2012
DOI: 10.3109/09638288.2012.690817
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of the World Health Organization Disability Assessment Schedule (WHODAS-II) in stroke

Abstract: WHODAS-II provides a reliable and valid instrument for measuring disability and components of "activities" and "participation" in stroke survivors. Various combinations of the item set may provide a range of scales to suit most research needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 28 publications
4
42
0
3
Order By: Relevance
“…More work is needed to further examine these discrepancies. Similarly, support for reliability is also consistent with other previously published studies that demonstrate that Cronbach’s alphas were good to excellent for the 36-item version [1; 46; 912; 14; 15; 17; 18; 21; 52]and good for the 12-item version [2]. Our examination of the reliability of the individual subscales indicated that, despite only 2 items per subscale, there was excellent internal consistency reliability for self-reported ADLs (i.e., Self-Care), good reliability for cognition and activities (i.e., Cognition and Life Activities), and adequate reliability for social engagement (i.e., Getting Along and Participation).…”
Section: Discussionsupporting
confidence: 90%
“…More work is needed to further examine these discrepancies. Similarly, support for reliability is also consistent with other previously published studies that demonstrate that Cronbach’s alphas were good to excellent for the 36-item version [1; 46; 912; 14; 15; 17; 18; 21; 52]and good for the 12-item version [2]. Our examination of the reliability of the individual subscales indicated that, despite only 2 items per subscale, there was excellent internal consistency reliability for self-reported ADLs (i.e., Self-Care), good reliability for cognition and activities (i.e., Cognition and Life Activities), and adequate reliability for social engagement (i.e., Getting Along and Participation).…”
Section: Discussionsupporting
confidence: 90%
“…This may have limited capacity to measure the extent to which patients have successfully resumed home and community responsibilities [37]. Besides FIM, other measures are currently available and might be useful to assess post-stroke patients [15,37,38].…”
Section: Study Limitationsmentioning
confidence: 99%
“…The Functional Independence Measure (FIM) is a functional assessment scale to assess self-care abilities, monitor the progress of rehabilitation and predict destination at discharge [9][10][11][12][13][14][15][16]. Numerous studies have demonstrated the usefulness and appropriateness of using FIM scores in the assessment of patients after acute stroke [4,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The WHODAS 2.0 has been used in the evaluation of disability caused by many conditions such as stroke, hand conditions, dementia, maternal complications, and psychiatric disorders . Regarding women's health, publications using ICF as a reference for functioning and disability are concentrated in oncology and maternal areas .…”
Section: Introductionmentioning
confidence: 99%
“…18 The World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) is a generic instrument that evaluates the difficulties that a person has experienced in social participation and daily activities in the last 30 days, and can be used in general population or groups with specific health conditions. 19 The WHODAS 2.0 has been used in the evaluation of disability caused by many conditions such as stroke, 20 hand conditions, 21 dementia, 22 maternal complications, 23 and psychiatric disorders. 24 Regarding women's health, publications using ICF as a reference for functioning and disability are concentrated in oncology [25][26][27][28][29] and maternal areas.…”
Section: Introductionmentioning
confidence: 99%